Praktyczne problemy oceny sytuacji finansowej zakładów ubezpieczeń - Prymon, Krzysztof (Practical Problems of the Assessment of the Financial Situation of Insurance Companies, 2007)
The purpose of the article is to present some problems connected with the financial situation of insurance companies. They are liable for general principles of accountancy of units. However, specificity of this kind of activity causes that the estimation of financial situation of these units have to take into consideration some specific elements of actuarial accountancy like e.g. specific institutional plan of company accounts, specific moment of incurring of costs and getting of income, agreement conclusion for long term, financial result established in two stagec, etc.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 418-423